2021
DOI: 10.3390/foods10051048
|View full text |Cite
|
Sign up to set email alerts
|

Black Soldier Fly (Hermetia illucens) Protein Concentrates as a Sustainable Source to Stabilize O/W Emulsions Produced by a Low-Energy High-Throughput Emulsification Technology

Abstract: There is a pressing need to extend the knowledge on the properties of insect protein fractions to boost their use in the food industry. In this study several techno-functional properties of a black soldier fly (Hermetia illucens) protein concentrate (BSFPC) obtained by solubilization and precipitation at pH 4.0–4.3 were investigated and compared with whey protein isolate (WPI), a conventional dairy protein used to stabilize food emulsions. The extraction method applied resulted in a BSFPC with a protein conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 59 publications
(149 reference statements)
2
22
0
1
Order By: Relevance
“…The peaks at 1647 cm −1 (amide I) and 1538 cm −1 (amide II) are indicative of α-helices conformation, and the presence of shoulder bands at 1626 cm −1 and 1517 cm −1 also indicates some degree of β-sheet secondary structure [ 34 ]. A more detailed analysis can be seen in Figure 2 B, where the Savitsky–Golay method and the second derivative were applied, similarly to a previous study on the protein concentrate of the black soldier fly [ 35 ]. The spectrum shows a qualitative analysis of the amide I region, correlated to C=O stretching.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peaks at 1647 cm −1 (amide I) and 1538 cm −1 (amide II) are indicative of α-helices conformation, and the presence of shoulder bands at 1626 cm −1 and 1517 cm −1 also indicates some degree of β-sheet secondary structure [ 34 ]. A more detailed analysis can be seen in Figure 2 B, where the Savitsky–Golay method and the second derivative were applied, similarly to a previous study on the protein concentrate of the black soldier fly [ 35 ]. The spectrum shows a qualitative analysis of the amide I region, correlated to C=O stretching.…”
Section: Resultsmentioning
confidence: 99%
“…A previous work reported the interfacial properties of black soldier fly protein concentrate (BSFPC) using a sunflower oil–water system to measure the decrease in IFT. The study reported that BSFCP instantaneously decreased IFT to 8.4 mN/m and reached 3.4 mN/m after 90 min of experiment [ 35 ]. The author used a 10 times higher protein concentration, 0.1% ( w / w ), compared to the concentration used in this study, 0.01% ( w / w ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nickel sieve had pores of 284.7 × 12.8 μm (length × width) with a thickness of 120 μm. Glass microbeads of 38 μm (0.44 g) were placed in the module on top of the nickel sieve, which resulted in 2 mm layer with an interstitial void diameter of ~22 μm, as calculated using the literature [ 43 ]. Coarse emulsions were placed in the vessel and immediately passed through the DMTS system pressurized to 500 kPa with N 2 ; this process is called one emulsification cycle.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, enzymatic hydrolysis of the protein extracts could efficiently enhance their functionalities and obtain bioactive peptides with antioxidative, antihypertensive, antidiabetic, and antimicrobial properties [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Regarding studies in emulsions stabilized with insect proteins, Wang et al [ 43 ] reported a superior performance of black soldier fly ( Hermetia illucens ) protein concentrate on emulsifying a high fraction (40 wt%) of lemon oil compared to whey protein isolate (WPI), and Gould and Wolf [ 44 ] found that sunflower oil emulsions stabilized with mealworm protein displayed smaller droplet size and a lower protein concentration was required compared to WPI; in addition, the produced emulsion also showed great stability under wide environmental stresses (temperature at −20 °C and 60–90 °C, pH 3–8 and ionic strength 80–330 mM). These results show the potential use of insect proteins to stabilize emulsions and are a good starting point to broaden their use to more complex systems, such as W 1 /O/W 2 emulsions.…”
Section: Introductionmentioning
confidence: 99%